Western diet-induced obesity results in brain mitochondrial dysfunction in female Ossabaw swine - Kelty, Taylor J.; Taylor, Chris L.; Wieschhaus, Nicole E.; Thorne, Pamela K.; Amin, Amira R.; Mueller, Christina M.; Olver, T. Dylan; Tharp, Darla L.; Emter, Craig A.; Caulk, Alexander W.; Rector, R. Scott (Frontiers in Molecular Neuroscience, 2023)
Diet-induced obesity is implicated in the development of a variety of neurodegenerative disorders. Concurrently, the loss of mitochondrial Complex I protein or function is emerging as a key phenotype across an array of neurodegenerative disorders. Therefore, the objective of this study was to determine if Western diet (WD) feeding in swine [carbohydrate = 40.8% kCal (17.8% of total calories from high fructose corn syrup), protein = 16.2% kcal, fat = 42.9% kCal, and 2% cholesterol] would result in Complex I syndrome pathology. To characterize the effects of WD-induced obesity on brain mitochondria in swine, high resolution respirometry measurements from isolated brain mitochondria, oxidative phosphorylation Complex expression, and indices of oxidative stress and mitochondrial biogenesis were assessed in female Ossabaw swine fed a WD for 6-months. In line with Complex I syndrome, WD feeding severely reduced State 3 Complex I, State 3 Complex I and II, and uncoupled mitochondrial respiration in the hippocampus and prefrontal cortex (PFC). State 3 Complex I mitochondrial respiration in the PFC inversely correlated with serum total cholesterol. WD feeding also significantly reduced protein expression of oxidative phosphorylation Complexes I–V in the PFC. WD feeding significantly increased markers of antioxidant defense and mitochondrial biogenesis in the hippocampi and PFC. These data suggest WD-induced obesity may contribute to Complex I syndrome pathology by increasing oxidative stress, decreasing oxidative phosphorylation Complex protein expression, and reducing brain mitochondrial respiration. Furthermore, these findings provide mechanistic insight into the clinical link between obesity and mitochondrial Complex I related neurodegenerative disorders.